Patch dynamics, persistence, and species coexistence in metaecosystems - Gravel, Dominique; Mouquet, Nicolas; Loreau, Michel; Guichard, Frédéric (The American naturalist, 2010)
We add an ecosystem perspective to spatially structured communities subject to colonization-extinction dynamics. We derive a plant-based metaecosystem model to analyze how the spatial flows of the biotic and abiotic forms of a limiting nutrient affect persistence and coexistence. We show that the proportion of patches supporting plants in a region has a considerable impact on local nutrient dynamics. Then we explicitly couple nutrient dynamics to patch dynamics. Our model shows strong feedback between local and regional dynamics mediated by nutrient flows. We find that nutrient flows can have either positive or negative effects on species persistence and coexistence. The essential feature of this local-regional coupling is the net direction of the nutrient flows between occupied and empty patches. A net flow of nutrients from occupied to empty patches leads to indirect facilitative interactions, such as an inferior competitor promoting the persistence of a superior competitor. We show that nutrient flows affect the potential diversity of the metaecosystem and key features of plant community dynamics, such as the shape of the competition-colonization trade-off and successional sequences. Our analysis revealed that integrating ecosystem and spatial dynamics can lead to various indirect interactions that contribute significantly to community organization.